Analisis Kekerasan Seksual di Lingkungan Kampus Menurut Perspektif Hukum dan Masyarakat - Manurung, Citra Bintang Maranatha; Ghufriani, Deliana Rinasari; Winata, Henry; Aulia, Meidina; Akbar, Muhamad Aria Torik; Sihombing, Oremia Exilla Rafelina; Pinasti, Putri; Aini, Qurrotul; Tetrya, Selvi; M, Mulyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Sexual violence on campus is a serious concern in society, with cases occurring that not only affect victims physically, but also psychologically. This research aims to understand the causes of sexual violence in the campus environment and the preventive measures taken by the campus. The research method used is library research. The causes of sexual violence on campus include an imbalance of power between the perpetrator and the victim, abuse of power by lecturers or campus officials, certain promises or lures given by the perpetrator to the victim, and a gender perspective that positions women always under men. Prevention of sexual violence on campus requires effective strategies, such as the establishment of a task force for the prevention and handling of sexual violence on campus and cooperation with external institutions or organizations that have expertise in handling cases of sexual violence. Periodic evaluation of prevention policies and programs is also important to ensure their effectiveness. Prevention of sexual violence on campus requires a joint effort from all relevant parties to create a safe and supportive campus environment for all its members